Pengaruh Corporate Social Responsibility (CSR) Terhadap Nilai Perusahaan Dengan Profitabilitas Sebagai Pemoderasi (Studi Empiris pada Perusahaan Go Publik yang Menjadi Peserta Asia Sustainability Reporting Rating (ASRRAT) yang Terdaftar di BEI Periode 2018-2022) - fadillah, marci; Hizazi, Achmad; Wijaya Z, Rico (Jurnal Akuntansi & Keuangan Unja, 2024)
This study aims to analyze the effect of Corporate Social Responsibility on company value with profitability as a moderating variable. This study uses a research sample of public companies that are participants in the Asia Sustainability Reporting Rating (ASRRAT) listed on the Indonesia Stock Exchange for the 2018-2022 period. The research data amounted to 110 companies for 5 periods. This research method uses historical methods and the research approach used is quantitative. This research is a comparative causal research which is an ex post facto research type. The collection of research data using tabulated data in the form of financial data obtained from financial reports. The data analysis technique in this study uses SPSS version 25. The results of the study indicate that Corporate Social Responsibility has an effect on company value, while profitability does not moderate the relationship between Corporate Social Responsibility and company value.